Superior Rice Cultivation as a Sustainable Agricultural - Gunawan Cipto Harsono; Moh. Ardani; Sumiarjo Kiswondo (Publisher Cv. Inara, 2021)
The purpose of this study was to determine the effect of variety and number of seeds on plant growth and yield in a sustainable agricultural cultivation system and to understand the interaction between variety and number of seeds on plant growth and yield in a sustainable agricultural cultivation system. This research design uses a qualitative approach, which is a research procedure and understanding based on a methodology that identifies a social phenomenon. This reseach study used the qualitative design. It is a constructivist paradigm in which reality is produced in context and social life, is exploratory, theory and development in the field, and depends more on data gathering in the field to expose the actual situation in the field. The result of this research were Analysis of the Interaction between Varieties and Number of Seeds on Rice Growth Using the Ciherang variety combined with the number of seeds 6 stems per clump, it is recommended to use the number of seeds 2 stems per clump when using the Mekongga variety. The second findings of this research were Rice Plants as Sustainable Agriculture via Cultivation and Conventional Approaches can be applied in a variety of agricultural areas throughout Indonesia. A business partnership through vertical consolidation is formed by using the appropriate business partnership strategy to encourage the development of agribusiness in rural areas.